Comprehensive genomic analysis of multidrug-resistant Pseudomonas aeruginosa isolates from companion animals in Germany - Bassiouny, Marwa; Brangsch, Hanka; Stamm, Ivonne; Kopp, Peter A.; Neubauer, Heinrich; Sprague, Lisa D. (Frontiers in Microbiology, 2026)
Pseudomonas (P.) aeruginosa is a highly adaptable, opportunistic nosocomial pathogen that poses significant risks to public health and veterinary medicine. This bacterium carries a wide range of antimicrobial resistance (AMR) determinants and produces various virulence factors that enable it to invade hosts and increase disease severity. Recognised as a One Health pathogen, P. aeruginosa can be isolated from multiple sources, including humans, animals, food, and the environment. Despite its importance in clinical settings, there are still limited genomic and epidemiological data on P. aeruginosa isolates from companion animals in Germany. To address this knowledge gap, we conducted whole-genome sequencing (WGS) of 72 P. aeruginosa isolates collected in 2023 from various companion animals, including dogs, cats, horses, and rabbits, across Germany. Phenotypic antibiotic susceptibility testing (AST) showed that 97.2% of the isolates exhibited a multidrug-resistant (MDR) phenotype. The highest resistance rates were observed for cefotaxime (98.6%), followed by chloramphenicol (93.1%) and trimethoprim/sulfamethoxazole (87.5%). Fosfomycin resistance was observed in 26.4% of the isolates, despite all isolates carrying the fosA gene. All isolates were found to be susceptible to colistin at increased exposure levels. Resistance to imipenem was detected in four dog isolates. Genome analysis revealed various AMR genes associated with resistance to β-lactams, aminoglycosides, sulfonamides, fluoroquinolones, and phenicols. Multiple virulence-associated genes were also identified, including those involved in biofilm formation, adherence, motility, immune modulation, and exotoxin A production. Moreover, 27.8% of the isolates carried plasmid contigs, and one dog isolate harboured a class 1 integron. In silico multilocus sequence typing (MLST) assigned the 72 isolates to 59 distinct sequence types (STs), including five novel STs (ST5165–ST5169). The most frequently identified STs were ST253, ST258, ST395, and ST244, each represented by three isolates. Six high-risk clones (HRCs) of P. aeruginosa, including ST308, ST277, ST244, ST395, ST253, and ST274, were identified in dog (n = 8) and cat (n = 4) isolates. This study underscores the significant genomic diversity of P. aeruginosa circulating among companion animals and emphasises the need to manage this bacterium within a One Health framework.